THE ROLE OF SPORTS IN THE UPBRINGING OF YOUNG PEOPLE WITH A HEALTHY LIFESTYLE - Sh.Z.Makulov (Scholar Express Journal, 2022)
This article discusses the role of sports in educating the younger generation to a healthy lifestyle. The author has justified the usefulness of sports from a medical and spiritual point of view
Keywords: sports; healthy lifestyle; physical education; spiritual education